2019
DOI: 10.4103/ijo.ijo_1146_18
|View full text |Cite
|
Sign up to set email alerts
|

Active-fluidics-based torsional phacoemulsification in diabetic eyes: A prospective interventional study

Abstract: Purpose: To compare the outcomes of active-fluidics based torsional phacoemulsification in diabetics and nondiabetics using a balanced tip. Methods: Two hundred and forty-eight patients undergoing senile cataract surgery using torsional phacoemulsification on an active-fluidics-based platform from December 2016 to August 2017 were included in this prospective, nonrandomized, interventional cohort study; of the 248 patients, 54 were controlled diabetics and 194 were nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These results suggested that even in cases of comparable CDE and EFU, the application of the AFS could reduce cornea injuries, with shorter postoperative recovery time and better early postoperative BCVA. The phenomenon might be related to the stable fluidics of the AFS, which is able to reduce turbulent flushing of the perfusate from damaging the corneal endothelium [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that even in cases of comparable CDE and EFU, the application of the AFS could reduce cornea injuries, with shorter postoperative recovery time and better early postoperative BCVA. The phenomenon might be related to the stable fluidics of the AFS, which is able to reduce turbulent flushing of the perfusate from damaging the corneal endothelium [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The global number of diabetic adults is expected to increase from 415 million to 642 million by 2040 [3][4][5]. Complications of diabetes are very different and impose serious damage to the heart, blood vessels, kidneys, nerves and eyes over time [6,7]. Ocular complications and changes in blood vessels cause damage to the retina in such way that the patient is not aware of the damage at an early stage [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in cataract surgery technology, postoperative complications are inevitable, of which, corneal edema is the most frequent. Exposure to surgical lights, thermal injury from US energy, the collision of nuclear debris and the washout of irrigation fluid are all causes of corneal damage [ 39 ]. When the corneal endothelium is damaged, its unique “pump” function will become impaired, which would increase water content in the corneal stroma, lead to corneal edema and result in vision loss [ 40 ].…”
Section: Performance Of Afs In Pkementioning
confidence: 99%
“…Accompanying that loss is the inability of the cornea to maintain its dehydrated state, which can lead to corneal edema and endothelial decompensation. During PKE, the US energy is the most vital and direct contributor to CEC damages [ 39 ]. Therefore, better efficiency and less CDE are goals to be pursued relentlessly.…”
Section: Afs In Complicated Conditionsmentioning
confidence: 99%
See 1 more Smart Citation